‘Desarrollo de una ficha integral para la empresa Impactex con el fin de optimizar y facilitar el proceso de producción - Cayambe López, Erika Lisbeth (2024)
The textile industry faces environmental challenges, serving as a significant source of pollution. To enhance operational efficiency, methods such as implementing comprehensive sheets, incorporating Activity-Based Costing and Theory of Constraints, aim to calculate precise costs and optimize production. Inventory management is crucial, linked to corporate social responsibility and occupational safety, emphasizing the need to improve practices in sectors with unpredictable inventory demands due to seasonal unpredictability. The objective of this work was to develop a comprehensive sheet for the company Impactex to optimize and streamline the production process. To conduct the project, interviews, observation sheets, and a checklist were utilized. As a result, it was determined that the technical sheet used by Impactex needs modification to meet the needs of the production department. It is concluded that certain details, such as supplier information, should be excluded to avoid competitive risks. Additionally, expanding color combinations in the sheets is suggested to enhance clarity in production. Observation sheets throughout the garment-making process identified technical and quality functions but indicated the need to implement additional details for maximum completeness.